Kawasaki disease for dermatologists - Aman Gupta; Surjit Singh (Wolters Kluwer Medknow Publications, 2016)
Kawasaki disease (KD) is a systemic vasculitis that mostly affects children below the age of 5. The vasculitis involves arteries of medium size, especially the coronaries. Various etiologies have been proposed including association with micro-organisms, bacterial superantigens, and genetic factors, however, the exact cause remains unknown. There is no specific laboratory test for KD. Diagnosis is clinical and depends upon the presence of fever for ≥5 days and 4 or more of five principal features, viz. polymorphous exanthem, extremity changes, mucosal changes involving the lips and oral cavity, bilateral bulbar conjunctival injection, and unilateral cervical lymphadenopathy. The term "incomplete KD" refers to the presence of fever and less than four principal clinical features. Recognition of this group of patients is important because it is usually seen in infants and risk of coronary abnormalities is increased probably because of delays in diagnosis. However, what appears to be "incomplete" at a given point of time may not actually be so because some of the features may have already subsided and others may evolve over time. Hence, a detailed dermatological examination is warranted in all cases, especially in incomplete KD, to ensure timely diagnosis. Although KD is a self-limiting disease in most patients, coronary artery abnormalities (CAAs) including coronary dilatations and aneurysms may develop in up to 25% of untreated patients. CAAs are the most common cause of morbidity and mortality in patients with KD. Treatment is aimed at reducing inflammation and consists of intravenous immunoglobulin (IVIG) along with aspirin. Despite treatment, some patients may still develop CAAs, and hence, long-term follow up is of utmost importance.